FDG PET in Intracranial Carcinomatous Meningitis. (January 2016) - Heimburger, Céline; Bund, Caroline; Namer, Izzie Jacques
Abstract : Abstract: A 63-year-old white man, diagnosed with pT3N2 squamous cell lung carcinoma, underwent right upper lobectomy with adjuvant radiochemotherapy. After a partial epileptic seizure, MRI revealed a solitary right frontal metastasis that was treated with surgical resection followed by stereotaxic radiotherapy. Three months later, the patient presented weight loss, weakness, and headache. He underwent a whole-body FDG PET/CT for restaging. It showed intense FDG uptakes on the brain periphery corresponding to nodular meningeal contrast enhancement on MRI leading to the diagnosis of carcinomatous meningitis, despite negative cerebrospinal fluid cytology.